2014
DOI: 10.1002/lary.24553
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss following ventriculoperitoneal shunt in communicating hydrocephalus patients: A pilot study

Abstract: Hearing thresholds may increase following VP shunt placement, possibly due to secondary endolymphatic hydrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Another study reported that hearing became normal after 3 years post-operatively. [8][9][10] A prospective study conducted by Lim et al 13 on nine patients with communicating hydrocephalus who underwent audiological testing before shunting, 5 days and 1 month after shunt placement. In 40% of patients, the pure tone threshold increased by at least 15 dB at one or more frequencies.…”
Section: Results Discussionmentioning
confidence: 99%
“…Another study reported that hearing became normal after 3 years post-operatively. [8][9][10] A prospective study conducted by Lim et al 13 on nine patients with communicating hydrocephalus who underwent audiological testing before shunting, 5 days and 1 month after shunt placement. In 40% of patients, the pure tone threshold increased by at least 15 dB at one or more frequencies.…”
Section: Results Discussionmentioning
confidence: 99%
“…There have been sporadic reports of temporary and permanent hearing loss after lumbar puncture, spinal anesthesia, and neurosurgeries [2][3][4][5] . Recently, Lim et al [6] reported an increased hearing threshold after elective VP shunt surgery. They argued that pressure changes in the CSF can induce pressure changes in the inner ear.…”
Section: Introductionmentioning
confidence: 99%